2014
DOI: 10.1186/1472-6831-14-61
|View full text |Cite
|
Sign up to set email alerts
|

Community-level assessment of dental plaque bacteria susceptibility to triclosan over 19 years

Abstract: BackgroundTriclosan is a broad-spectrum antimicrobial agent used in toothpaste to reduce dental plaque, gingivitis and oral malodor. This community-level assessment evaluated the susceptibility of dental plaque bacteria to triclosan in samples collected over 19 years.MethodsA total of 155 dental plaque samples were collected at eleven different times over 19 years from 58 adults using 0.3% triclosan, 2% copolymer, 0.243% sodium fluoride toothpaste and from 97 adults using toothpaste without triclosan. These in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(45 reference statements)
1
5
0
2
Order By: Relevance
“…Si bien el cepillado es el método más eficaz para el control de la placa (Axelsson et al, 1991), la evidencia señala que la utilización de coayudantes como los colutorios colabora significativamente en la reducción de la placa bacteriana en población juvenil (Haraszthy et al, 2014). Entre los componentes utilizados en colutorios comercializados se encuentra el alcohol, triclosán y la clorhexidina (Pereira et al, 2014) entre otros que pueden generar efectos no deseados en el tratamiento, tales como la alteración del sabor, manchas en los dientes (Salgado et al, 2006) o cálculos supragingivales (Aspalli et al) afectando funcional y estéticamente a los pacientes.…”
Section: Discussionunclassified
“…Si bien el cepillado es el método más eficaz para el control de la placa (Axelsson et al, 1991), la evidencia señala que la utilización de coayudantes como los colutorios colabora significativamente en la reducción de la placa bacteriana en población juvenil (Haraszthy et al, 2014). Entre los componentes utilizados en colutorios comercializados se encuentra el alcohol, triclosán y la clorhexidina (Pereira et al, 2014) entre otros que pueden generar efectos no deseados en el tratamiento, tales como la alteración del sabor, manchas en los dientes (Salgado et al, 2006) o cálculos supragingivales (Aspalli et al) afectando funcional y estéticamente a los pacientes.…”
Section: Discussionunclassified
“…In 2014, Haraszthy et al. reported on a study of 155 dental plaque samples that were collected at 11 different times over 19 years. Fifty‐eight of the 155 subjects from whom the plaque samples had been collected had used triclosan toothpaste for at least 5 years, whilst 97 had used a toothpaste that did not contain triclosan.…”
Section: Dentifricesmentioning
confidence: 99%
“…But, clinical relevance in multiple studies for bacterial resistance has not been demonstrated for about 50 years of long-term repeated use of triclosan [ 2 , 3 , 49 – 52 ]. In one individual long-term clinical study there was no alteration in oral antimicrobial resistance from patients using 0.3% triclosan with the copolymer PVM/MA for at least 5 years [ 53 , 54 ]. Several government reports from large groups of authorities in the field have determined that although cross-resistance to antimicrobials or antibiotics can be demonstrated under artificial laboratory conditions, the development of resistance in natural or clinical environments with complex multiple bacterial species was not an equivalent condition for the use of triclosan [ 2 , 3 , 49 ].…”
Section: Bacterial Resistance To Triclosan Not Seen Under Normal Cmentioning
confidence: 99%